1981
DOI: 10.1093/infdis/143.1.63
|View full text |Cite
|
Sign up to set email alerts
|

A New Animal Model for the Study of Chlamydia trachomatis Genital Infections: Infection of Mice with the Agent of Mouse Pneumonitis

Abstract: A new animal model for the study of genital infections caused by Chlamydia trachomatis has been developed. Female mice were successfully infected after intravaginal inoculation with the C. trachomatis agent of mouse pneumonitis. Evidence for infection was obtained by detection of chlamydial inclusions in smears of cervical scrapings treated with Giemsa stain. Chlamydiae were observed in sections of cervical tissues examined by light and electron microscopy as well as by immunofluorescence microscopy. An antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 12 publications
1
95
1
Order By: Relevance
“…Further, different human isolates do not have equal abilities to produce salpingitis in mice, implying a genetic component to the infectivity of these isolates. Intravaginal inoculation of mice with the agent of mouse pneumonitis (MoPn; a C. trachomatis biovar) results in cervical infection, and chlamydial inclusions are found in superficial cervical epithelial cells (Barron et al, 1981). Recently it has been shown that inoculation directly into the ovarian bursa of these mice consistently results in salpingitis (Swenson et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Further, different human isolates do not have equal abilities to produce salpingitis in mice, implying a genetic component to the infectivity of these isolates. Intravaginal inoculation of mice with the agent of mouse pneumonitis (MoPn; a C. trachomatis biovar) results in cervical infection, and chlamydial inclusions are found in superficial cervical epithelial cells (Barron et al, 1981). Recently it has been shown that inoculation directly into the ovarian bursa of these mice consistently results in salpingitis (Swenson et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are many well-characterized inbred and knockout mouse strains available (18). The female mouse genital tract is susceptible to infection with both Chlamydia muridarum (9) and C. trachomatis (10), which has resulted in the establishment of two murine models: the C. trachomatis mouse model and the C. muridarum mouse model.…”
Section: Mouse Modelsmentioning
confidence: 99%
“…Another commonly used mouse model of Chlamydia infection is to inoculate female mice in the vaginal vault with the species Chlamydia muridarum, often designated as the mouse pneumonitis agent MoPn. Although C. muridarum is not a human pathogen, genital infection of mice with C. muridarum phenotypically mimics many aspects of C. trachomatis genital infection in humans (Barron et al, 1981;Everett et al, 1999). Interestingly, C. muridarum is largely resistant to the inhibitory effects of IFN-g in both murine cell lines and in vivo mouse models (Rottenberg et al, 2002;Nelson et al, 2005).…”
Section: Innate Immunity To C Trachomatismentioning
confidence: 99%